Giving patients their own records in general practice: experience of patients and staff. Issue 6520 (1st March 1986) - Baldry, M; Cheal, C; Fisher, B; Gillett, M; Huet, V
Abstract : Patients have reacted positively to seeing their medical records in a general practice which has a predominantly working class population in south east London. Most patients were familiar with the information in their records. Older people tended to avoid reading their notes. There have been few inaccuracies and unpleasant reactions reported, and few problems have arisen.